Mental Healing in Korean Drama “It's Okay to Not Be Okay - Heidy Arviani; Natasya Candraditya Subardja; Jessica Charisma Perdana (Universitas Islam Balitar, 2021)
This study aims to describe adult mental healing, which is represented in the Korean drama series